Growth Module in the Pediatric Preclerkship Educational Exercises (PRECEDE) Curriculum - David W. Cooke; Eric Balighian; Stacy Cooper; Michael Barone; Robert Dudas; Emily Frosch; Justin Jeffers; Rosalyn Stewart; W. Christopher Golden (Association of American Medical Colleges, 2018)
Introduction The Johns Hopkins Pediatrics Clerkship developed this growth module as part of the PRECEDE (preclerkship educational exercises) curriculum, with the primary goal of providing students with experiential, explicit, and standardized instruction in essential pediatric clinical skills to better prepare them to utilize these skills during their clerkship. Methods This 2-hour growth module begins with a 45-minute didactic overview of growth, including discussion of normal growth, normal variants of growth, and disorders that affect growth, and contains interactive elements to engage the students. Students then divide into groups of four to six, each with a faculty facilitator to work through three cases in a guided discussion to explore specific aspects of growth that may be encountered in a pediatric evaluation. Results In a survey of 238 students, 97-100% agreed or strongly agreed with eight positive assessments of the module. Likewise, 79% of students rated the module as excellent, the remainder rating the module as good. Discussion From the perspectives of students and instructors, the implementation of this new module was very successful in its delivery of educational content. These cases were designed to give the students experience in plotting growth parameters against normative data and to gain familiarity with pediatric growth curves in order to identify growth abnormalities. The cases also aimed to reinforce the importance of using growth data in pediatric patients in order to both generate a differential diagnosis for a growth disorder and to modify a differential diagnosis generated by a chief complaint based on growth data.